Fundamentals of biophysics - Rubin, A. B. (Andreĭ Borisovich) (Scrivener Publishing, John Wiley and Sons, 2014)
"Biophysics is a science that comprises theoretical plotting and models based on contemporary physicochemical conceptions. They mirror physical specificity of the molecular organization and elementary processes in living organisms, which in their turn form the molecular basis of biological phenomena. Presentation of a complete course in biophysics requires vast biological material as well as additional involvement of state-of-the-art concepts in physics, chemistry and mathematics. This is essential for the students to "perceive" the specific nature and peculiarity of molecular biological processes and see how this specificity is displayed in biological systems. This is the essence of the up-to-date biophysical approach to the analysis of biological processes. Fundamentals of Biophysics offers a complete, thorough coverage of the material in a straightforward and no-nonsense format, offering a new and unique approach to the material that presents the appropriate topics without extraneous and unneeded filler material"--EBL